The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1152/ajpendo.00065.2001
|View full text |Cite
|
Sign up to set email alerts
|

Altered corticosteroid metabolism differentially affects pituitary corticotropin response

Abstract: To evaluate the effects of altered corticosteroid metabolism on the hypothalamic-pituitary-adrenal axis, we examined rats treated with glycyrrhizic acid (G rats) or rifampicin (R rats) for 7 days. The half-life of exogenously administered hydrocortisone as a substitute for corticosterone was longer in G rats and shorter in R rats, with no differences in basal plasma levels of ACTH or corticosterone. The ACTH responses to human corticotropin-releasing factor (CRF) or insulin-induced hypoglycemia were greater in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…It has been reported that administration of GA decreases CRH release into the hypophysial portal blood without changing circulating glucocorticoid levels [13]. In this regard, Hanafusa et al [12] found that mRNA expression and the levels of CRH in the hypothalamus did not change in GA-treated rats. This study, however, demonstrated up-regulation of CRH receptor mRNA and binding levels in the pituitary of the GA-treated animals, suggesting that GA enhanced the ACTH response to CRH by increasing the number and/or sensitivity of CRH receptors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that administration of GA decreases CRH release into the hypophysial portal blood without changing circulating glucocorticoid levels [13]. In this regard, Hanafusa et al [12] found that mRNA expression and the levels of CRH in the hypothalamus did not change in GA-treated rats. This study, however, demonstrated up-regulation of CRH receptor mRNA and binding levels in the pituitary of the GA-treated animals, suggesting that GA enhanced the ACTH response to CRH by increasing the number and/or sensitivity of CRH receptors.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study showed alterations in the pituitaryadrenal response in vivo in rats treated with GA [12]. On the basis of this result we carried out CRH tests to investigate the course of pseudoaldosteronism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…81 In cases of long term hypothyroidism which can lead to hypoadrenalism and decreased cortisol levels, hydrocortisone (5 mg twice a day) or licorice (240 mg glycyrrhizin twice a day) may be efficacious. 82 Both hydrocortisone and licorice should be given upon rising and around noon to mimic the natural circadian rhythm. As licorice can lead to blood pressure elevation in some users, blood pressure monitoring is recommended while following this protocol.…”
Section: To T 3 Conversionmentioning
confidence: 99%
“…In contrast, 11HSD2 operates as a strict dehydrogenase that oxidizes corticosterone and cortisol to 11-oxo-derivatives [7]. 11HSD1 is expressed in the brain [8][10], pituitary [11], [12], adrenal gland [13], and many peripheral organs including the spleen, thymus, and lymphatic nodes [14], [15].…”
Section: Introductionmentioning
confidence: 99%